A place to exist : the true and untold story of Camp Hope and homelessness in Spokane - Smith, Maurice (Rising River Media, 2023)
"A Place To Exist is the story of Camp Hope, the largest homeless camp in the State of Washington, from its inception in December of 2021 to its successful closure in June of 2023. Located on right-of-way property owned by the Washington State Department of Transportation along I-90 in Spokane, Camp Hope became the perfect storm of 689 people experiencing unsheltered homelessness in Spokane with no place to exist. A Place To Exist is a treasure trove of lessons learned about policy failures that created Camp Hope and the practical steps needed to successfully close the camp by moving the unsheltered homeless from chaos to cosmos and to personal shalom. The lessons learned and implemented at Camp Hope have become a model for state and local officials working to successfully resolve homeless camps throughout the State of Washington" -- Back cover.